Institutional Support of Innovative R&D in the Formation of Single Research Area in the EU and Ukraine - Matyushenko, I.Yu.; Khaustova, V.Ye.; Kniaziev, S.I. (Science and Innovation, 2024)
The necessity of developing innovation ecosystems as common tools of research and innovation management under rapid growth of interdisciplinary research in the most high-tech industries of the world leading countries has been established. Paradigm of the creation of the European research area based on the three priorities (open science, open innovation and regional smart specialization) has been analyzed. Proposals to the National Action Plan for actualizing the Ukrainian research space based on implementation of the Roadmap for the Creation of Single European Research Area for 2015-2020 and to the draft Strategy for the Development of High-Tech Industries of Ukraine until 2025 have been elaborated.